Waste Management Model Analysis - Yusril Ihsani; Arif Zainudin; Akhmad Habibullah (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2026)
The problem of waste is becoming an increasingly complex environmental issue due to increasing population, economic activity, and consumption patterns of society. This study aims to analyze the impact, scope, and models of waste management through a review of the scientific literature. The method used is Systematic Literature Review (SLR) with a bibliometric approach using scientific article data from the Scopus database, period 2015-2025. The process of identifying and selecting literature is carried out using the PRISMA protocol to ensure the research is conducted in a systematic, structured, and transparent manner. A total of 711 articles were declared eligible for analysis in this review. Data analysis was conducted using Biblioshiny in RStudio to map the relevance of research themes. The results showed that waste management has a significant impact on improving environmental quality, controlling soil, water, and air pollution, and protecting public health. The scope of waste management includes source reduction, sorting, collection, transportation, processing, and final disposal, as well as technological and policy aspects. Effective waste management models are integrated and aligned with the principles of sustainability and the circular economy, thereby supporting reduced waste generation and more efficient resource use.